Assessment of Pollution Index of Cu, Cd and Pb in Soil Environment in the Intensive Cultivation Areas of Vegetables, Flower in Tay Tuu Ward, Bac Tu Liem District, Hanoi - Huan, Nguyen (VNU Journal of Science: Earth and Environmental Sciences, 2017)
Accumulation of heavy metals in the soil environment due to intensive agriculture can lead to the potential risk of contamination for not only the soil environment but also the public health. However, the researches in Vietnam only conducted with the assessment of the concentration of heavy metals in the soil and comparision with the national standard. This paper conducted the assessment of pollution for three heavy metals (Cu, Cd and Pb) by applying single index and intergarted pollutant index. The results showed that the concentrations of heavy metals (Cu, Cd, and Pb) in most analyzed samples were exceeded the recommendation values for the maximum content of total heavy metals in topsoil for agricultural land. But the polluted index of heavy metal pollutants (Cu, Cd, Pb) varied from low, moderately polluted level to slightly polluted levels depending on the application of the index.